TULIP2: An Improved Method for the Identification of Ubiquitin E3-Specific Targets - Salas-Lloret, Daniel; Agabitini, Giulia; González-Prieto, Román (Frontiers in Chemistry, 2019)
Protein modification by Ubiquitin or Ubiquitin-like modifiers is mediated by an enzyme cascade composed of E1, E2, and E3 enzymes. E1s, or ubiquitin-activating enzymes, perform ubiquitin activation. Next, ubiquitin is transferred to ubiquitin-conjugating enzymes or E2s. Finally, ubiquitin ligases or E3s catalyze the transfer of ubiquitin to the acceptor proteins. E3 enzymes are responsible for determining the substrate specificity. Determining which E3 enzyme maps to which substrate is a major challenge that is greatly facilitated by the TULIP2 methodology. TULIP2 methodology is fast, precise, and cost-effective. Compared to the previous TULIP methodology protocol, TULIP2 methodology achieves a more than 50-fold improvement in the purification yield and two orders of magnitude improvement in the signal-to-background ratio after label free quantification by mass spectrometry analysis. The method includes the generation of TULIP2 cell lines, subsequent purification of TULIP2 conjugates, preparation, and analysis of samples by mass spectrometry.